Use of haploid biotechnology for production of new highly productive cultivars of Triticum aestivum L. (Experimental biology, 2015)
By using of haploid biotechnologies in vitro are received valuable DHL-lines of a winter wheat which have surpassed on productivity and on quality of grain of parental grades or the standard. From DHL lines has been selected the new highly productive cultivar of wheat under the name "Nureke" which has been zoned in Almaty and Zhambyl region is created.
Keywords: haploid biotechnology; culture of microspores in vitro; Triticum aestivum L.